2020
DOI: 10.1111/zph.12700
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vector competence of Aedes vexans Green River and Culex pipiens biotype pipiens for West Nile virus lineages 1 and 2

Abstract: West Nile virus (WNV), a zoonotic arbovirus, has recently established an autochthonous transmission cycle in Germany. In dead-end hosts like humans and horses the WNV infection may cause severe symptoms in the central nervous system. In nature, WNV is maintained in an enzootic transmission cycle between birds and ornithophilic mosquitoes. Bridge vector species, such as members of the Culex pipiens complex and Aedes spp., also widely distributed in Germany, might transmit WNV to other vertebrate host species. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Other studies also showed that the viremia that can be expected in WNV-infected chickens is not higher than the blood meal titers that we used [51,52]. In addition, the amount of ingested viral RNA detected in day 0 controls was not lower than in other vector competence studies where mosquito infection was successful [49,53]. Thus, the blood meal titer does not appear to be the reason of the low positivity rates.…”
Section: Discussionsupporting
confidence: 52%
“…Other studies also showed that the viremia that can be expected in WNV-infected chickens is not higher than the blood meal titers that we used [51,52]. In addition, the amount of ingested viral RNA detected in day 0 controls was not lower than in other vector competence studies where mosquito infection was successful [49,53]. Thus, the blood meal titer does not appear to be the reason of the low positivity rates.…”
Section: Discussionsupporting
confidence: 52%
“…Tis indicates that our chosen blood meal titer was not decisive for this result. In a previous study, the colony "Green River" was already tested for its vector competence for WNV lineages 1 and 2 [70]. Infection rates of Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Aedes vexans were found positive for WNV for the first time in Romania. Studies of vector competence have shown the ability of this species to transmit WNV [ 38 , 39 ]. However, its mammophilic character suggests that Aedes vexans could play only a minor role in WNV transmission, unlike the ornitophilic/generalist Culex pipiens s.l., which is the main WNV vector and was repeatedly found infected in natural and anthropic areas from the east and southeast of the country [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%